Prediabetes and its impact on cardiovascular health: A review article - Buitrago-Gómez, Nathalia; Figueroa, Lunevar; Casanova, María Eugenia (Universidad y Salud, 2022)
Introduction: Prediabetes is an intermediate state of hyperglycemia with a high prevalence in the Colombian population. The relationship between prediabetes and cardiovascular disease as well as its association with macro and microvascular complications has been established, with scientific evidence increasing in recent literature. Objective: To describe cardiovascular diseases (macrovascular complications) related to prediabetes, their diagnosis, physiopathology, management approach, and treatment to prevent those complications. Materials and methods: A narrative review of the literature was conducted, searching for scientific articles in Medline during the 2015-2021 period. Results: 83 articles were selected, which described the relationship between prediabetes with cardiovascular disease, mortality, diagnosis, and treatment based on recent reports. Conclusions: The importance of prediabetes lies in its association with macrovascular complications and its mortality. This association highlights the importance of studying, monitoring, and treating this disease to avoid its progression to diabetes mellitus, the development of outcomes that end in increased morbidity and mortality, diminished quality of life, and increased health care costs.